Fair Internal Mediation: A Humanist Approach To Employment Dispute Resolution At PT. Nafasindo - Ismaidar Ismaidar; RR Sasmaya Hati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to discuss in depth the mediation process in resolving industrial relations disputes at PT Nafasindo, as well as examine the legal policy of PT Nafasindo in resolving industrial relations disputes. The type of research used is normative juridical with a descriptive-analytical approach, discussing existing legal symptoms and problems and testing them based on laws and regulations and legal norms. The results of this study show that the internal mediation process includes several stages, namely: receiving complaint reports from the police and directly, the summons stage, the appointment of a mediator, mediation sessions, the preparation of agreements, and the follow-up of mediation results. Mediators in mediation take an effective humanist approach in resolving workers' disputes with the company, as they produce solutions based on the best fairness for the parties. PT Nafasindo's legal policy in industrial relations disputes (non-litigation) with employees is to prioritize a consensus deliberation approach, involve internal mediators in resolving problems, apply fair rules of non-discrimination, uphold work professionalism, involve workers in decision-making, and employee welfare programs.